Developing Explore C-Play: A Game-Based E-Worksheet for Cambridge Lower Secondary English Learners - Harbiah Hilda Amalia; Ulfa Wulan Agustina (English Language Education Department, Universitas Majalengka, 2026)
This research aimed to develop an interactive digital learning medium entitled Explore C-Play (English Practice, Lower Secondary Assessment with Cambridge Playful Learning) based on e-worksheet for international students at Aqobah International School. The research employed a Research and Development (R&D) design using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were lower secondary international students, while the data were collected through needs analysis, expert validation, interviews, and questionnaires. The developed product integrates gamebased activities using the LiveWorksheets platform to support four English skills: listening, speaking, reading, and writing, in accordance with the Cambridge Curriculum and Playful Learning approach. The results of the study indicated that Explore C-Play is feasible and effective as a learning medium. Material expert validation reached 93%, categorized as excellent, while media expert validation obtained 81%, categorized as very good. In addition, students’ responses showed a very positive perception with an average score of 98%, indicating high motivation, engagement, and interest in learning English through the developed e-worksheet. These findings demonstrate that game-based digital worksheets can enhance students’ participation and understanding in English learning. Therefore, Explore C-Play can be used as an effective supporting learning medium for international lower secondary students implementing the Cambridge Curriculum.